2004
DOI: 10.1074/jbc.m313318200
|View full text |Cite
|
Sign up to set email alerts
|

Helix Orientation of the Functional Domains in Apolipoprotein E in Discoidal High Density Lipoprotein Particles

Abstract: Human apolipoprotein E (apoE) mediates high affinity binding to the low density lipoprotein receptor when present on a lipidated complex. In the absence of lipid, however, apoE does not bind the receptor. Whereas the x-ray structure of lipid-free apoE3 N-terminal (NT) domain is known, the structural organization of its lipidassociated, receptor-active conformation is poorly understood. To study the organization of apoE amphipathic ␣-helices in a lipid-associated state, single tryptophan-containing apoE3 varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 48 publications
11
79
0
Order By: Relevance
“…The calculated helical content of ADPH(172-425) in aqueous solution was 53%. Its degree of helicity increased to 61% after incubation in 50% trifluoroethanol, suggesting that unstructured regions of the recombinant protein may have additional helix formation potential in a membrane-like environment (36). These initial experiments support our homology model and demonstrate that ADPH(172-425) is an independently folding structure with significant ␣-helical nature.…”
Section: Adenoviral Expression Of Gfp-adph(1-220) In Mammarysupporting
confidence: 74%
“…The calculated helical content of ADPH(172-425) in aqueous solution was 53%. Its degree of helicity increased to 61% after incubation in 50% trifluoroethanol, suggesting that unstructured regions of the recombinant protein may have additional helix formation potential in a membrane-like environment (36). These initial experiments support our homology model and demonstrate that ADPH(172-425) is an independently folding structure with significant ␣-helical nature.…”
Section: Adenoviral Expression Of Gfp-adph(1-220) In Mammarysupporting
confidence: 74%
“…In addition, complexing with DMPC resulted in formation of discrete lipid particles with diameters in the range of 18 nm. Based on previous studies, it is known that these particles exist as disk-shaped phospholipid bilayers wherein two or more apoE-NT molecules circumscribe the disk perimeter through interaction with phospholipid fatty acyl chains [16,17].…”
Section: Apoe-nt•dmpc Disk Particle Formationmentioning
confidence: 99%
“…We conclude that excimer fluorescence arose from intramolecular proximity between R61C and E255C in the context of reconstituted lipoprotein particles. In recent investigations, several lines of evidence indicated formation of discoidal phospholipid bilayer complexes of DMPC/apoE3, with the ␣-helices circumscribing the periphery of the particles (30,49,50). Furthermore, examination of VLDL-and HDL-bound pyr-R61C/E255C/apoE4 revealed excimer fluorescence (Fig.…”
Section: Effect Of Lipid Interaction Of Pyr-r61c/e255c/apoe4 On Pyrenmentioning
confidence: 99%
“…7). In previous studies, it was suggested that apoE3 undergoes a dramatic conformational alteration upon lipid interaction, involving movement of the two domains away from each other (30,56), accompanied by further opening of the helix bundle (49,57) to yield a fully extended molecule circumscribing the periphery of discoidal bilayer of phospholipids (50). In the case of apoE4, we propose that a similar movement of the two domains about the hinge region occurs; however, spatial proximity between Arg-61 and Glu-255 is re-established upon lipid interaction, yielding a looped-back arrangement of helices.…”
Section: Effect Of Lipid Interaction Of Pyr-r61c/e255c/apoe4 On Pyrenmentioning
confidence: 99%